Cytokine level in patients with mood disorder, alcohol use disorder and their comorbidity. (16th March 2023) - Mednova, Irina A.; Levchuk, Lyudmila A.; Boiko, Anastasiia S.; Roschina, Olga V.; Simutkin, German G.; Bokhan, Nikolay A.; Loonen, Anton J. M.; Ivanova, Svetlana A.
Abstract: Objectives: Because alcohol use disorder (AUD) is often accompanied by mood disorder (MD) and both alcoholism and depression result in activation of the immune system, this study compares serum cytokine levels in the presence of co-morbidity with those in either AUD or MD alone. Methods: In this naturalistic prospective study the levels of 15 different cytokines were measured in serum samples of patients with MD ( n  = 43), participants with combined AUD-MD ( n  = 44) and AUD without MD ( n  = 42). The levels were compared cross-sectionally among themselves and with those in 50 healthy volunteers. Results: Pro-inflammatory IFN-2α levels were consistently significantly higher and anti-inflammatory IL-1RA significantly lower in all study groups in comparison to healthy volunteers. In the MD only group we found increased IL-6 ( p  = 0.001), IL-7 ( p  = 0.001) and IL-13 ( p  = 0.006) levels, and decreased TNFα ( p  = 0.0001), IL-1RA ( p  = 0.012), IL-10 ( p  = 0.002) compared with group MD + AUD. Patients with AUD only showed elevated levels of IL-1β ( p  = 0.046), IL-2 ( p  = 0.004), IL-7 ( p  = 0.0001), IL-4 ( p  = 0.049) and IL-13 ( p  = 0.015) in contrast with MD + AUD group. Conclusions: Because the interactions of alcohol with peripheral and cerebral immune systems are multifaceted, the pertinent connection to the mechanism how alcohol consumption contributes to the development of mood disorders cannot be properly explored.